(3Gdjejfjs - (3GdYJHj , eMeO Hf YHO GdLHGQ GdQGRj GdTGaYj,J (B427 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdXGgQ HBjGJg GdHGWf (B((3HYO gPG eXdeI SjFI GdJUhjQ(B) s
(3aj JGQjN jejf GdOhdI eMehO Hf SHcJcjfs
(3YdjgG hbajI SfI (B1067 (3g`s
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B184 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B10 - (3U (B126s
Keywords: (3GdJGQjNs